Training spatial intelligence in football through the cognitive load scale - Pedrosa, Rafael; Tavares, Ricardo (Frontiers in Sports and Active Living, 2025)
Cognitive skills like working memory and spatial awareness play a central role in football, yet they are not commonly addressed in training. Here, we propose a practical approach to integrating cognitive demands into football practice without losing the ecological validity of the game. We introduce the Cognitive Load Scale (CLS), a five-level framework to classify and adapt drills based on their cognitive demands. Through task constraints involving space, color rules, attentional shifts, and memory load, coaches can challenge how players perceive, decide, and act under pressure. We present examples across CLS levels, showing how spatial intelligence can be trained systematically on the pitch. The goal is to design sessions where the game itself becomes the tool for cognitive development.